Beneficial bacterial-Auricularia cornea interactions fostering growth enhancement identified from microbiota present in spent mushroom substrate - Phithakrotchanakoon, Chitwadee; Mayteeworakoon, Sermsiri; Siriarchawatana, Paopit; Kitikhun, Supattra; Harnpicharnchai, Piyanun; Wansom, Supaporn; Eurwilaichitr, Lily; Ingsriswang, Supawadee (Frontiers in Microbiology, 2022)
Complex dynamic bacterial-fungal interactions play key roles during mushroom growth, ranging from mutualism to antagonism. These interactions convey a large influence on mushroom’s mycelial and fruiting body formation during mushroom cultivation. In this study, high-throughput amplicon sequencing was conducted to investigate the structure of bacterial communities in spent mushroom substrates obtained from cultivation of two different groups of Auricularia cornea with (A) high yield and (B) low yield of fruiting body production. It was found that species richness and diversity of microbiota in group (A) samples were significantly higher than in group (B) samples. Among the identified 765 bacterial OTUs, 5 bacterial species found to exhibit high differential abundance between group (A) and group (B) were Pseudonocardia mangrovi, Luteimonas composti, Paracoccus pantotrophus, Sphingobium jiangsuense, and Microvirga massiliensis. The co-cultivation with selected bacterial strains showed that A. cornea TBRC 12900 co-cultivated with P. mangrovi TBRC-BCC 42794 promoted a high level of mycelial growth. Proteomics analysis was performed to elucidate the biological activities involved in the mutualistic association between A. cornea TBRC 12900 and P. mangrovi TBRC-BCC 42794. After co-cultivation of A. cornea TBRC 12900 and P. mangrovi TBRC-BCC 42794, 1,616 proteins were detected including 578 proteins of A. cornea origin and 1,038 proteins of P. mangrovi origin. Functional analysis and PPI network construction revealed that the high level of mycelial growth in the co-culture condition most likely resulted from concerted actions of (a) carbohydrate-active enzymes including hydrolases, glycosyltransferases, and carbohydrate esterases important for carbohydrate metabolism and cell wall generation/remodeling, (b) peptidases including cysteine-, metallo-, and serine-peptidases, (c) transporters including the ABC-type transporter superfamily, the FAT transporter family, and the VGP family, and (d) proteins with proposed roles in formation of metabolites that can act as growth-promoting molecules or those normally contain antimicrobial activity (e.g. indoles, terpenes, β-lactone, lanthipeptide, iturin, and ectoines). The findings will provide novel insights into bacterial-fungal interactions during mycelial growth and fruiting body formation. Our results can be utilized for the selection of growth-promoting bacteria to improve the cultivation process of A. cornea with a high production yield, thus conveying potentially high socio-economic impact to mushroom agriculture.